Intention and Target of Religion-Based Hate Speech in A Decade of Judicial Decisions - Diah Imaningrum Susanti; Fidelis Aggiornamento Saintio; Justin Wejak (Jurnal Hukum dan Peradilan, 2026)
The meaning of Religion-based Hate Speech can be explored deeply through the judge's considerations in linking these two issues: freedom to express religious beliefs and the target of the RHS. This research examines how Indonesian judges interpret the RHS in two ways: 1) Did the perpetrator accused of committing religion-based hate speech really have the intention to blaspheme religion? 2) Who is the target in cases of RHS the religion itself, the adherents of the religion, or other parties? The research database includes cases that have permanent legal force for 10 years (2016-2025). The legal materials were collected by downloading decisions related to the RHS that have permanent legal force and have been officially posted on the Supreme Court website. Secondary legal materials are authoritative texts written to interpret or discuss primary legal materials. In the cases analyzed, the perpetrators' intentions were not the only consideration in the judicial decisions. When a speech is considered a religion-based hate speech and becomes a case that is tried, the judge considers the elements that were violated, in this context, namely, creating a commotion and causing hostility. Furthermore, remarks deemed to be religion-based hate speech are those that "offend a religion or belief," and they were linked to protests or demonstrations by followers.